Wpływ regulacji prawnych na źródła kapitału funduszy private equity - Fałat-Kilijańska, Ilona (The Law Regulations Influence on Sources of Private Equity Finance, 2005)
The article shows the major sources of Polish private equity funds compared to the developed private equity markets (in the countries of the European Union and in the United States of America). The author presents how the law regulations can affect the private equity market growth, activate domestic capital (especially from pension funds) and direct to small and medium sized firms. Readers can also find many interesting examples how governments can affect the suply of private equity funds.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 21-32